Trial outcomes and information for clinical decision-making: a comparative study of opinions of health professionals. Issue 1 (December 2016) - McNair, Angus; Brookes, Sara; Whistance, Robert; Forsythe, Rachael; Macefield, Rhiannon; Rees, Jonathan; Jones, James; Smith, George; Pullyblank, Anne; Avery, Kerry; Thomas, Michael; Sylvester, Paul; et al.
Abstract Background Trials are robust sources of data for clinical practice; however, trial outcomes may not reflect what is important to communicate for decision-making. The study compared clinicians' views of outcomes to include in a core outcome set for colorectal cancer (CRC) surgery, with what clinicians considered important information for clinical practice (core information). Methods Potential outcome/information domains were identified through systematic literature reviews, reviews of hospital information leaflets and interviews with patients. These were organized into six categories and used to design a questionnaire survey that asked surgeons and nurses from a sample of CRC centers to rate the importance of each domain as an outcome or as information on a nine-point Likert scale. Respondents were re-surveyed (round 2) following group feedback (Delphi methods). Comparisons were made by calculating the difference in mean scores between the outcomes and information domains, and pairedt tests were used to explore the difference between mean scores of the six outcome/information categories. Results Data sources identified 1216 outcome/information items for CRC surgery that informed a 94-item questionnaire. First-round questionnaires were returned from 63/81 (78 %) of centers. Clinicians rated 76/94 (84 %) domains of higher importance to measure in trials than information to communicate to patients in round 1. This was reduced to 24/47 (51 %) in round 2. The greatest difference was evident in domains regarding survival, which was rated much more highly as a trial outcome than an important piece of information for decision-making (difference in mean 2.3, 95 % CI 1.9 to 2.8, p <0.0001). Specific complications and quality-of-life domains were rated similarly (difference in mean 0.18, 95 % CI −0.1 to 0.4, p = 0.2 and difference in mean 0.2, 95 % CI −0.1 to 0.5, p = 0.2, respectively). Conclusions Whilst clinicians want to measure key outcomes in trials, they rate these as less important to communicate in decision-making with patients. This discrepancy needs to be explored and addressed to maximize the impact of trials on clinical practice.